Isolated Vaginal Agenesis Associated with Multiple Gastrointestinal Anomalies: A Case Report - Angotti, Rossella; Molinaro, Francesco; Bulotta, Anna Lavinia; Ferrara, Francesco; Sica, Marina; Bindi, Edoardo; Messina, Mario (Journal of Neonatal Surgery, 2016)
More than 50% of infants with esophageal atresia have associated anomalies. We present a case report of a 46XX neonate with long-gap esophageal atresia and tracheoesophageal fistula (EA/TEF), anorectal malformation, bowel duplication and vaginal agenesis. This is an unusual association of abnormalities which had not yet described in literature.